2015
DOI: 10.3892/ijo.2015.3254
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of transient receptor potential cation channel, subfamily C, member 1 contributes to drug resistance and high histological grade in ovarian cancer

Abstract: Abstract. Transient receptor potential cation channel, subfamily C, member 1 (TRPC1) participates in many physiological functions but has also been implicated in cancer development. However, little is known about the role of TRPC1 in ovarian cancer (OC), including the drug resistance of these tumors. In the present study, a significant and consistent downregulation of TRPC1 in drug-resistant OC tissues/cells was determined using real-time quantitative polymerase chain reaction assays and the microarrays deposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 92 publications
1
20
0
Order By: Relevance
“…Possible networks of protein or gene interactions with KCNN3 included 49 gene or gene products associated with drug-resistance in OC, which further explained its association with drug resistance. These genes/gene products included 25 oncogenes ( 35 ); URI1, STAT3, SRC, RSF1, PIK3CA, NOTCH3, NINL, NFKB1, MYC, MIEN1, MET, KRAS, JUN, IKBKE, FOS, ERBB2, EGFR, DAXX, CUZD1, CLU, BCL2, BAX, AKT2, AKT1 and ACTN4 and 15 tumor suppressors ( 36 ) including BRCA1, BRCA2, CHEK2, FBXO32, MLH1, SULF1, IL24, CDKN2A, CDKN1A, TP53, TP73, PDCD4, PTEN, RASSF1 and WWOX, as well as 9 other genes, including CCL21 and SPARCL1 ( 37 ), GGNBP2 and RNASET2 ( 38 ), NEK2 ( 39 ), NEK11 ( 40 ), ALDH1A2 and ADH1B ( 41 ) and TRPC1 ( 42 ). KCNN3 directly interacted with 18 of these genes or gene products, and exhibited indirect interactions with the rest ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Possible networks of protein or gene interactions with KCNN3 included 49 gene or gene products associated with drug-resistance in OC, which further explained its association with drug resistance. These genes/gene products included 25 oncogenes ( 35 ); URI1, STAT3, SRC, RSF1, PIK3CA, NOTCH3, NINL, NFKB1, MYC, MIEN1, MET, KRAS, JUN, IKBKE, FOS, ERBB2, EGFR, DAXX, CUZD1, CLU, BCL2, BAX, AKT2, AKT1 and ACTN4 and 15 tumor suppressors ( 36 ) including BRCA1, BRCA2, CHEK2, FBXO32, MLH1, SULF1, IL24, CDKN2A, CDKN1A, TP53, TP73, PDCD4, PTEN, RASSF1 and WWOX, as well as 9 other genes, including CCL21 and SPARCL1 ( 37 ), GGNBP2 and RNASET2 ( 38 ), NEK2 ( 39 ), NEK11 ( 40 ), ALDH1A2 and ADH1B ( 41 ) and TRPC1 ( 42 ). KCNN3 directly interacted with 18 of these genes or gene products, and exhibited indirect interactions with the rest ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, acquisition of drug resistance in multiple myeloma is associated with the suppression of inositol 1,4,5-triphosphate receptor type 1, phospholipase C, transient receptor potential cation channel subfamily M member 7 and TRPC1 expression, and reducing the expression of TRPC1 markedly inhibits drug-induced cell death ( 51 ). It was observed that decreased expression of TRPC1 is associated with drug resistance in OC ( 42 ), and the protein interacts with KCNN3. Thus, it was concluded that low expression of KCNN3 may contribute to drug resistance via interactions with TRPC1, through inhibition of drug induced cell death.…”
Section: Discussionmentioning
confidence: 99%
“…In this analysis, in the case of two probe sets that target one gene, only the probe set with significant variability was retained. In the case of more than three probe sets that target one gene, the set exhibiting the most divergent expression was excluded and the set with significant variability was retained (12).…”
Section: Gene Expression Profilesmentioning
confidence: 99%
“…Moreover, the altered expression profile of various members of the TRPC subfamily has been associated with chemoresistance. For instance, TRPC1 expression is significantly decreased in cisplatin-resistant (A2780 and SKOV3) and carboplatin-resistant (A2780) ovarian cancer cell lines, suggesting that the reduced expression of TRPC1 is linked to chemoresistance [169]. On the contrary, TRPC5 has increased in 5-FU-resistant colorectal cancer cells HCT-8/5-FU and LoVo/5-FU cell lines, therefore blockade of TRPC5 promotes chemosensitivity in these cells [170].…”
Section: Trpcmentioning
confidence: 99%